2008
DOI: 10.1016/j.cgh.2008.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Endoscopy Nurse Experience and Polyp Detection During Screening Colonoscopy

Abstract: Background & Aims-The effect of GI endoscopy nursing experience on polyp detection is unknown. The aim of this study was to determine whether nurse experience is associated with odds of polyp detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…In accordance with previous studies, the findings of the current study suggest that a high rate of nurse turnover may have a potential negative impact on colonoscopy outcomes. 22,26 Therefore, we believe in seeking practical means to support and retain experienced endoscopy nurses. We categorized the level of endoscopy nurse experience according to work-years in the GI endoscopy unit.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In accordance with previous studies, the findings of the current study suggest that a high rate of nurse turnover may have a potential negative impact on colonoscopy outcomes. 22,26 Therefore, we believe in seeking practical means to support and retain experienced endoscopy nurses. We categorized the level of endoscopy nurse experience according to work-years in the GI endoscopy unit.…”
Section: Discussionmentioning
confidence: 98%
“…26 The same investigators, in a retrospective analysis of 3631 colonoscopies, also reported that procedures staffed by more experienced endoscopy nurses (Ն6 months) have increased odds of detecting colon polyps (OR 1.26; 95% CI, 1.09-1.46), but the role of endoscopy nurses in their study was limited to sedation, monitoring the patient, and assistance with the procedure. 22 Several pilot studies have examined the learning curve for nurse endoscopists performing flexible sigmoidoscopy and colonoscopy. [27][28][29] However, the effect of GI endoscopy nurse participation on lesion detection, which is the primary goal of colonoscopy, has not been previously reported in a prospective setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The preamble of the guideline claimed that the medical literature was searched using PubMed; yet, a search using the keywords nurse and colonoscopy yielded a number of studies reporting the outcomes of nurses performing colonoscopy. [2][3][4][5][6] For readers to critically appraise, reproduce, and perhaps update the guidelines, it would be useful if such guidelines included the search details (database, keywords used, and period of search). We are concerned that, in an era of increased need for colorectal cancer screening and subsequent surveillance, the role and potential of nurse colonoscopists might have been minimized by an incorrect level-3 recommendation, instead of being capitalized upon as a precious resource.…”
Section: Studies Of Nurses Performing Colonoscopy Have Been Performedmentioning
confidence: 99%
“…It has been our clinical experience that all aspects of the procedure may be facilitated by experienced endoscopy nurses, especially colonoscopy performed during gastroenterology fellowship training. Furthermore, trainees or a second, non-physician (nurse or technician) participation as an additional observer may be associated with polyp and adenoma detection 13-15. A previous retrospective study reported that procedures staffed by nurses with ≤6 months of endoscopy nursing experience had 1.26-fold likelihood of not detecting a polyp compared with nurses with more experience 13.…”
Section: Introductionmentioning
confidence: 99%